Cover Picture: Plasma Process. Polym. 11/2018. Issue 11 (16th November 2018) - Nolan, Hugo; Sun, Daye; Falzon, Brian G.; Chakrabarti, Supriya; Padmanaba, Dilli Babu; Maguire, Paul; Mariotti, Davide; Yu, Tao; Jones, David; Andrews, Gavin; Sun, Dan
Abstract : Front Cover: The development of multifunctional nanocomposite materials is of great interest for various biomedical applications. A popular approach to produce tailored nanocomposites is to incorporate functional nanoparticles into hydrogels. A benign atmospheric pressure microplasma synthesis approach has been deployed for the synthesis of metal and alloy NP/PVA hydrogels. Practical applications of the NP/PVA nanocomposites have been demonstrated by anti‐bacterial testing, showing their potential for a range of biomedical applications. Further details can be found in the article by Hugo Nolan, Daye Sun, Brian Falzon, et al. (e1800112 )